Changes in energy use patterns in the Bushbuckridge Lowveld of the Limpopo Province, South Africa: eleven years on - Madubansi, Mainza (Rhodes University, Faculty of Science, Department of Environmental Science, 2004)
This research reports on the energy transition that has taken place in the Bushbuckridge district between 1991 and 2002. It is a follow up to a similar study that was done in 1991 investigating a number of aspects of energy use. It uses the 1991 study as a baseline and aims to explore how the passage of time, growth of the local population and changes in incomes and the availability of fuels have affected the patterns of fuel use in the region in the past eleven years. A structured interview approach was used for most aspects of the study. The interview schedule included sections on types, amounts and reasons for use and non-use of 13 different energy sources as well as data on income levels, household size and other economic parameters. Analysis of the consumption patterns of the different fuel types revealed that between the two survey periods, households in the sample settlements went through some pronounced changes in patterns of fuel use, particularly those that had acquired electricity. The introduction of electricity in the region had certainly played a major role in spurring the energy transition. Fuels that were previously used for lighting, powering entertainment appliances and refrigeration had been displaced by electricity. In terms of cooking and other thermal application, however, the vast majority of households in all the sample settlements continued using fuelwood and complemented it to a lesser extent with paraffin and electricity. In both surveys, the use or non-use of available fuels in the region was influenced by several factors. Common reasons for non-use of certain fuel types included expense, lack of appliances, the risk involved in using such fuels and the preference for other fuels. Reasons for use were mainly related to the low cost of the fuel and the fuel's ability to meet particular end uses. Although incomes in the region had increased between 1991 and 2002, they were still below the poverty line. Activities from which households obtained their income remained the same. Old age pension, migrant wages and the informal sector remained the largest contributors of income to most households. Other indicators of relative wealth and poverty, like ownership of vehicles, bicycles and beds remained the same.
Keywords: Energy consumption -- South Africa -- Limpopo